Transforming Waste Management in Egypt Through Extended Producer Responsibility in Automotive and Transportation - H. Abdelati, Mohamed; Abdelwali, Hilal A.; Matar, Al-Hussein; M. Rabie (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
The policy proposal of Extended Producer Responsibility in Egypt’s automotive and transportation industry is discussed in this research as a viable solution for major waste management issues. From the best practices observed on the international level and having regard to the country-specific socio-economic environment of Egypt, the study suggests comprehensive and step-by-step anatomy that might be best adapted to adoption in the given country context. Simulations for hypothetical modeling on some of the main automobile components including tires and batteries, indicated that recycling rates could rise from an initial 10% to over 50% after 10 years under EPR. The framework also points to the creation of approximately 15,000 new jobs and the achievement of 20% cost savings on municipal waste management. One of the most important elements is the capacity to support the participation of informal waste pickers in the formal system, providing them with the training and motivation, that will secure an environmentally sound approach, as well as social inclusion. This work therefore provides a clear guideline for policymakers and stakeholders to SMADE to implement an effective, reflective, and fair manner of waste management which complements Egypt’s Vision 2025 and other Universal sustainable developments.